An evaluation of students’ motivation in computer-supported collaborative learning of programming concepts. - Serrano-Cámara, Luis Miguel; Paredes-Velasco, Maximiliano; Alcover, Carlos-María; Velazquez-Iturbide, J. Ángel (Computers in Human Behavior, 2014)
Highlights: [•] This is the first study on motivation using CSCL for programming education. [•] Students are more motivated by using CIF+MoCAS than by collaborative learning. [•] CIF and MoCAS are associated with high levels of intrinsic and extrinsic motivation. [•] Unexpectedly, CIF and MoCAS also are associated with amotivation.